MRI and 1H-MRS in adenosine kinase deficiency - Staufner, Christian; Kölker, Stefan; Hoffmann, Georg F.; Harting, Inga (Neuroradiology, 2016)
IntroductionAdenosine kinase deficiency (ADK deficiency) is a recently described disorder of methionine and adenosine metabolism resulting in a neurological phenotype with developmental delay, muscular hypotonia, and epilepsy as well as variable systemic manifestations. The underlying neuropathology is poorly understood. We have investigated MRI and 1H-MRS changes in ADK deficiency in order to better understand the in vivo neuropathologic changes of ADK deficiency.MethodsSystematic evaluation of 21 MRIs from eight patients (age range 9 days-14.6 years, mean 3.9 years, median 2.7 years) including diffusion-weighted imaging in six and 1H-MRS in five patients.ResultsBrain maturation was delayed in the neonatal period and in infancy (6/6), but ultimately complete. White matter changes occurring in five of eight patients were discrete, periventricular, and unspecific (4/5), or diffuse with sparing of optic radiation, corona radiata, and pyramidal tracts (1/5). Choline was low in white matter spectra (3/3), while there was no indication of low creatine in white matter or basal ganglia (5/5), and diffusion was variably decreased or increased. Central tegmental tract hyperintensity was a common finding (6/8), as was supratentorial atrophy (6/8).ConclusionsMRI changes in ADK deficiency consist of delayed but ultimately completed brain maturation with later onset of mostly unspecific white matter changes and potentially transient central tegmental tract hyperintensity. Immaturity on neonatal MRI is consistent with prenatal onset of disease and reduced choline with lower membrane turnover resulting in delayed myelination and deficient myelin maintenance.
Gesehen am 11.02.2019
Im Titel ist "1" im 1H-MRS hochgestellt